'La Comunitá La Vela': a psychoanalytically oriented approach to eating disorders - Vilanova,Andrea (2012)
The authors discuss the experience of treating eating disorders at a psychoanalytically oriented therapeutic community in Italy. Teamwork and group activities are the bases of the treatment, at least to the point that the experience of the collectivity does not hinder the individual subjective expression of each patient. The treatment includes several different steps in the process of the admittance and release of patients and the subjectivation involved in the process is considered very important. A clinical vignette is presented at the end of the article.